Global Weak Solutions for the Weakly Dissipative μ-Hunter–Saxton Equation - Liu, J. (Український математичний журнал, 2013)
The paper deals with the global existence of weak solutions for a weakly dissipative μ-Hunter–Saxton equation. The problem is analyzed by using smooth data approximating the initial data and Helly’s theorem. Розглянуто проблему глобального існування слабких розв'язків слабкодисипативного μ-рівняння Хантера- Сакстона за допомогою гладких даних, що є наближенням до початкових даних, та теорему Хеллі.